Rural youth's exposure to firearm violence and their attitudes regarding firearm safety measures - Charles A. Jennissen; Ryan P. King; Kristel M. Wetjen; Gerene M. Denning; Cole C. Wymore; Nicholas R. Stange; Pamela J. Hoogerwerf; Junlin Liao; Kelly E. Wood (BMC, 2021)
Abstract Background In the wake of an epidemic in firearm-related deaths and injuries, youth have become leading voices of concern. This study's objective was to investigate rural youth's personal experiences with firearm-related violence, and their attitudes towards firearms and gun violence prevention strategies. Methods Attendees of the 2019 Iowa FFA Leadership Conference were surveyed about personal experiences with firearm-associated deaths and injuries, and their attitudes regarding firearm-related issues. Descriptive (frequencies), bivariate (chi square, Fisher's exact test) and multivariable logistic regression analyses were performed utilizing Stata 15.1 (StataCorp, College Station, Texas). Results Responses from 1382 FFA members 13-18 years of age were analyzed. About 5% had personally seen someone threatened with a firearm. Over one-third (36%) stated they knew someone who had been killed or injured by gunfire. Of these, over two-thirds knew of someone who had died or was injured unintentionally and 30% knew of someone killed or injured intentionally (e.g. suicide). Nearly all agreed or strongly agreed that the right to use firearms for hunting and shooting sports should be legal (94%), that a firearm safety course should be required to get a hunting license (89%), and that there should be a required background check before purchasing a firearm (89%). Over three-fifths (61%) agreed or strongly agreed that there should be laws requiring safe storage of firearms in homes. Although still high, lesser support for firearm safety policies was seen among males, older youth, participants living on farms or in the country, and youth who hunted, had firearms in their homes, and/or were in homes with unsafe firearm storage. Conclusions The majority of youth in this study supported firearm safety measures including required training, background checks, and safe firearm storage in homes. These findings are consistent with the national youth-led call for firearm safety. Additionally, over one-third of respondents personally knew someone who was killed or injured by a firearm and 5% had seen someone or been personally threatened with firearm violence. Our study did not investigate the effects of firearm violence on participants' mental health and wellbeing, but future studies addressing this question seem highly justified.